Temporal Response of Endogenous Neural Progenitor Cells Following Injury to the Adult Rat Spinal Cord - Mao, Yilin (Front Cell Neurosci, 2016)
A pool of endogenous neural progenitor cells (NPCs) found in the ependymal layer and the sub-ependymal area of the spinal cord are reported to upregulate Nestin in response to traumatic spinal cord injury (SCI). These cells could potentially be manipulated within a critical time period offering an innovative approach to the repair of SCI. However, little is known about the temporal response of endogenous NPCs following SCI. This study used a mild contusion injury in rat spinal cord and immunohistochemistry to determine the temporal response of ependymal NPCs following injury and their correlation to astrocyte activation at the lesion edge. The results from the study demonstrated that Nestin staining intensity at the central canal peaked at 24 h post-injury and then gradually declined over time. Reactive astrocytes double labeled by Nestin and glial fibrillary acidic protein (GFAP) were found at the lesion edge and commenced to form the glial scar from 1 week after injury. We conclude that the critical time period for manipulating endogenous NPCs following a spinal cod injury in rats is between 24 h when Nestin expression in ependymal cells is increased and 1 week when astrocytes are activated in large numbers.